2011
DOI: 10.1002/jsfa.4475
|View full text |Cite
|
Sign up to set email alerts
|

RIN transcription factor plays an important role in ethylene biosynthesis of tomato fruit ripening

Abstract: The syringe infiltration method of VIGS was successfully applied to silence the LeRIN, LeACS2, LeACS4 and LeACO1 genes in tomato fruits. In addition, the target genes of RIN transcription factor in ethylene biosynthesis were identified. The results are critical for understanding the mechanism of ethylene biosynthesis in tomato fruit ripening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…in both rin and Nr mutants indicated that these genes would be regulated by RIN directly or via ethylene during ripening, thus confirming findings reported earlier as well as in this report (Lin et al 2008;Martel et al 2011). The absence of ACS2 and ACS4 genes among genes downregulated in Nr mutant and the presence of ACO1 in microarray data of genes downregulated in both the mutants confirms the earlier findings that RIN does not directly regulate ACO1 gene but it regulates ACS2 and ACS4 genes directly, hence, suggesting that microarray data of rin and Nr might be useful to identify the putative targets for RIN protein (Ito et al 2008;Fujisawa et al 2011;Li et al 2011a, b).…”
Section: Identification Of New Regulators Of Ethylene Responses and Esupporting
confidence: 91%
See 2 more Smart Citations
“…in both rin and Nr mutants indicated that these genes would be regulated by RIN directly or via ethylene during ripening, thus confirming findings reported earlier as well as in this report (Lin et al 2008;Martel et al 2011). The absence of ACS2 and ACS4 genes among genes downregulated in Nr mutant and the presence of ACO1 in microarray data of genes downregulated in both the mutants confirms the earlier findings that RIN does not directly regulate ACO1 gene but it regulates ACS2 and ACS4 genes directly, hence, suggesting that microarray data of rin and Nr might be useful to identify the putative targets for RIN protein (Ito et al 2008;Fujisawa et al 2011;Li et al 2011a, b).…”
Section: Identification Of New Regulators Of Ethylene Responses and Esupporting
confidence: 91%
“…Induction of ripening-associated genes involved in ethylene biosynthesis, such as ACS1A, ACS2, ACS4, and ACO1, in wild-type fruit is in accordance with the earlier findings while inhibition in their expression in the rin mutant fruits explained as to why no climacteric production of ethylene is observed in fruits of the rin mutant (Lincoln et al 1993;Barry et al 1996Barry et al , 2000Nakatsuka et al 1998;Vrebalov et al 2002;Yokotani et al 2004;Li et al 2011a, b). Modulated expression of genes encoding three ethylene receptors proteins (ETR3-5) as well as downstream components of ethylene signal pathways, such as TCTR1, 4, EIN2, EIL1, 2, 4 and several ERFs suggests that ethylene signal transduction also gets affected during fruit development in the rin mutant.…”
Section: Identification Of New Regulators Of Ethylene Responses and Esupporting
confidence: 86%
See 1 more Smart Citation
“…EMSA was performed according to Li et al using non‐radioactive EMSA kits. ChIP was achieved in accordance with the protocol of the ChIP assay kit and by the method of Li et al Polymerase chain reactions (PCRs) were performed using appropriate primers: CPACO4 F, CPACO4 R, CPα ‐Gal F, CPα ‐Gal R, CPActin F and CPActin R (Table ). PCR products were detected on 2% agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…The protein spots in gels were digested with trypsin according to Shevchenko et al 30 LC/MS/MS analysis was carried out in accordance with the methods of Qin et al 27 and Chen et al 31 EMSA and ChIP assay EMSA was performed according to Li et al 32 using non-radioactive EMSA kits. ChIP was achieved in accordance with the protocol of the ChIP assay kit and by the method of Li et al 32 Polymerase chain reactions (PCRs) were performed using appropriate primers: CPACO4 F, CPACO4 R, CP -Gal F, CP -Gal R, CPActin F and CPActin R ( Table 1). PCR products were detected on 2% agarose gels.…”
Section: Determination and Verification Of Proteins Of Polyacrylamidementioning
confidence: 99%